2008
DOI: 10.1186/1471-2253-8-3
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study to evaluate the accuracy of pulse power analysis to monitor cardiac output in critically ill patients

Abstract: BackgroundIntermittent measurement of cardiac output may be performed using a lithium dilution technique (LiDCO). This can then be used to calibrate a pulse power algorithm of the arterial waveform which provides a continuous estimate of this variable. The purpose of this study was to examine the duration of accuracy of the pulse power algorithm in critically ill patients with respect to time when compared to measurements of cardiac output by an independent technique.MethodsPulse power analysis was performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…Patients received one or more fluid challenges according to the clinical prescription. calibrated with an injection of lithium chloride (0.3 mmol) given according to the manufacturer's recommendation (18,19). Beat-to-beat CO and stroke volume (SV) was obtained with LiDCO TM plus pulse power analysis (20).…”
Section: Methodsmentioning
confidence: 99%
“…Patients received one or more fluid challenges according to the clinical prescription. calibrated with an injection of lithium chloride (0.3 mmol) given according to the manufacturer's recommendation (18,19). Beat-to-beat CO and stroke volume (SV) was obtained with LiDCO TM plus pulse power analysis (20).…”
Section: Methodsmentioning
confidence: 99%
“…However, the system needs to be calibrated using transpulmonary lithium indicator dilution technique, which can be performed via a peripheral venous line [8]. Clinical studies have demonstrated reliable estimation of CO using this technique as long as no major hemodynamic changes are observed [9,10]. The reliability of the LiDCOplus system may be negatively affected by changes of electrolytes and hematocrit and by high peak doses of muscle relaxants, which crossreact with the lithium sensor.…”
Section: The Lidco Systemsmentioning
confidence: 98%
“…Th erefore, the LiDCO systems should be considered as pulse power analysis techniques. Th e LiDCO TM plus requires calibration using the transpulmonary lithium indicator dilution technique, which can be performed via a peripheral venous line [12]. In contrast, the LiDCO TM rapid uses nomograms for cardiac output estimation.…”
Section: Pulse Pressure Analysismentioning
confidence: 99%